ナンキョクカイ インドヨウ ク ノ クロロフィルα リョウ - 山県, 健二; ヤマガタ, ケンジ; 福井, 深; フクイ, フカシ; Yamagata, Kenji; Fukui, Fukashi (1981)
P(論文) 1979年12月から1980年3月まで, 水産庁開洋丸により, 南極海調査航海が実施され, その際, 海水中のクロロフィルa量の測定を行った。フリマントル～61°S, 100°E間の往路(1/7～1/15)と61°S, 120°E～メルボルン間の復路(1/27～2/8)では表面海水中のクロロフィルa量を測定した。往路, 復路のクロロフィルa量はそれぞれ0.05-0.44mg/m^3,0.02-0.18mg/m^3を示し, 復路に比べ, 往路の方が高い値を示した。61°S以南100°-120°Eの調査水域では5本の測線にそった36点において表層から200m層までの10層のクロロフィルa量を測定した。調査水域のクロロフィルa量は0.00-0.95mg/m^3の範囲を示し, 特に0.5mg/m^3以上の水塊が亜表層にコア状に分布していた。そしてそのクロロフィルa極大は, ほとんどの地点で密度躍層付近で観測された。 Measurement of chlorophyll a in the Indian sector of the Antarctic Ocean was carried out during the cruise of R. V. KAIYO MARU of the Fisheries Agency, from December 1979 to March 1980. The chlorophyll a content in the surface water was measured at stations from Fremantle to the station of 61°S, 100°E (1/7-1/15,1980) and from the station of 61°S, 120°E to Melbourne (1/27-2/8,1980). The surface water chlorophyll a content in the former course ranged from 0.05 to 0.44mg/m^3,and in the latter it ranged from 0.02 to 0.18mg/m^3. Surface water chlorophyll a was larger on the outward leg than on the homeward leg. The chlorophyll a content at 36 stations which were arranged along five transections in the survey area was measured on water samples taken from 10 layers between the surface and the depth of 200m. The chlorophyll a content ranged from 0.00 to 0.95mg/m^3. The water mass which contained more than 0.5mg/m^3 chlorophyll a could be regarded as a core in the subsurface water. The chlorophyll a peaks were observed near the picnocline at most of the stations. departmental bulletin paper